PERANAN PERUSAHAAN BATUBARA TERHADAP PEREKONOMIAN MASYARAKAT SANGGATA KABUPATEN KUTAI TIMUR (STUDI KASUS PT. KALTIM PRIMA COAL) - Marita Sombo (ADMINISTRASI PUBLIK, 2020)
This study aims to determine the economic conditions of the community and mining workers as well as to determine the impact of the existence of a coal mining company for residents around the mine. This research uses descriptive qualitative research by providing a clear and systematic picture related to the object under study in order to provide valid information and data related to facts and phenomena in the field. The approach used in this study is the approach of sociology and psychology, and uses data collection techniques by conducting observations, interviews, and documentation to obtain information from informants.The results of research and discussion show that: 1) The dynamics of the community in the mine area can be known from the economic conditions of the community, since the existence of a mining company the lives of residents can be said to have changed dramatically, and with the existence of a mining company has opened wide employment opportunities for residents around the mining area. 2) Mining activities managed by KPC are already very environmentally friendly and prioritize residents around the mine. Post mining aside from reforestation, it is also used for fish farming. The positive impacts are: a) Sources of foreign exchange. b) Sources of Regional Original Revenue (PAD). c) Accommodate workers.The implications of this research are: There needs to be more serious attention and supervision from my stakeholders in environmental management efforts and environmental monitoring efforts or studies on Environmental Impact Analysis (AMDAL) both in formulating policies relating to mining activities, before mining activities are carried out. it can be predicted in advance the impact on the environment.